Estimating antibiotics consumption in a tertiary care hospital in Islamabad using a WHO’s defined daily dose methodology - Jabeen, Naila; Ullah, Waseem; Khalid, Javeria; Samad, Zia (Antimicrobial resistance & infection control, 2023)
Antibiotics have helped to reduce the incidence of common infectious diseases in all modern healthcare systems, but improper use of antibiotics including their overuse and misuse can change the bacteria so much that antibiotics don't work against them. In case of developing imposable selective pressure with regard to the proportion of hospitalized patients who receive antibiotics, the quantity of antibiotics that are prescribed to them, and the proportion of patients who receive antibiotic treatment is one of the major contributors to the rising global health issue of antimicrobial resistance. Concerning the levels of antibiotic consumption in Pakistani hospitals, there is negligible research data available. This study aimed to evaluate five-year inpatient antibiotic use in a tertiary care hospital in Islamabad using the World Health Organization (WHO) Recommended Anatomical Therapeutic Chemical (ATC) Classification / Defined Daily Dose (DDD) methodology. It was a descriptive study involving a retrospective record review of pharmacy records of antibiotics dispensed (amount in grams) to patients across different specialties of the hospital from January 2017 to December 2021 (i.e., 60 consecutive months). The antibiotic consumption was calculated by using the DDD/100-Bed Days (BDs) formula, and then relative percent change was estimated using Microsoft Excel 2021 edition. A total of 148,483 (77%) patients who received antibiotics were included in the study out of 193,436 patients admitted in the hospital. Antibiotic consumption trends showed considerable fluctuations over a five-year period. It kept on declining irregularly from 2017 to 2019, inclined vigorously in 2020, and then suddenly dropped to the lowest DDD/100 BDs value (96.02) in the last year of the study. The overall percentage of encounters in which antibiotics were prescribed at tertiary care hospital was 77% which is very high compared to the WHO standard reference value (< 30%). WATCH group antibiotics were prescribed (76%) and consumed more within inpatient settings than Access (12%) and Reserve (12%) antibiotics. The hospital antibiotic consumption data is well maintained across different inpatient specialties but it is largely non-aligned with WHO AWaRe (Access-Watch-Reserve) antibiotics use and optimization during 2017-2021. Compared to the WHO standard reference figure, the overall percentage of antibiotics encountered was higher by about 47%. Antibiotic consumption trends vary with a slight increase in hospital occupancy rate, with positive relative changes being lower in number but higher in proportion than negative changes. Although the hospital antibiotics policy is in place but seems not to be followed with a high degree of adherence.